The Impact of Covid-19 Work Related Factors on Employees’ Productivity - Lee Kwee Fah; Kwan Xiao Jun; Yeong Wai Mun; Ung Leng Yean; Foo Meow Yee (Universitas Internasional Batam, 2023)
For the past few years, many businesses have been suffering from sales decline as they struggled to manage their employees during the Covid-19 outbreak. As a result, many companies today have policies to deal with the epidemic, such as the implementation of hybrid work arrangements to manage employee contact. Operating performance remains crucial for businesses to survive and flourish. Working from home requires self-discipline as there are less interactions with superiors, which can negatively affect employee productivity. Therefore, effective management is critical to maintain or improve employees’ productivity level. The effect of remote work arrangements on the productivity of the general workforce have not been fully explored particularly in Malaysia. Literature review on work productivity during Covid-19 reveals that studies have mainly focussed employees in health and education sectors. The review of Malaysia indicates on that work from home productivity studies have mostly centred on a specific workplace or industry. Notably, there are no existing studies regarding the work from home productivity of the general workforce comprising of employees from both the manufacturing and service sectors in Malaysia. Therefore, this study aims to fill the research gap by focussing on the general workforce in Malaysia who are mostly employed either in the service or manufacturing sector. It is important for business organizations to understand the relevant Covid-19 work-related factors that impact the productivity of their staff. The factors are perceived organizational support, leadership, teamwork and technology support. For this study, data was collected via online survey. In total, 150 useable responses were obtained and analysed using SPSS. The results show that perceived organizational support and technology support significantly impact work productivity. However, leadership and teamwork did not have significant effect on employees’ productivity. These findings provide a useful guidance to managers to focus on providing organizational and technological support in order to improve work productivity for employees involved in hybrid working mode.